Current delivery limitations of proton PBS for FLASH. (February 2021) - Zou, Wei; Diffenderfer, Eric S.; Cengel, Keith A.; Kim, Michele M.; Avery, Steve; Konzer, Joshua; Cai, Yongliang; Boisseu, Paul; Ota, Kan; Yin, Lingshu; Wiersma, Rodney; Carlson, David J.; et al.
Highlights: FLASH proton PBS has strong potential to be implemented for patient treatment. Clinical proton PBS delivery parameters were extrapolated to high cyclotron current. It is challenging to achieve >40Gy/s FLASH dose rate for field size >4x4 cm 2 . Scanning magnet slew and energy switching times appear to be the limiting factors. Portion of the local dose can be delivered at FLASH dose rate. Abstract: Purpose: Proton Pencil Beam Scanning (PBS) is an attractive solution to realize the advantageous normal tissue sparing elucidated from FLASH high dose rates. The mechanics of PBS spot delivery will impose limitations on the effective field dose rate for PBS. Methods: This study incorporates measurements from clinical and FLASH research beams on uniform single energy and the spread-out Bragg Peak PBS fields to extrapolate the PBS dose rate to high cyclotron beam currents 350, 500, and 800 nA. The impact of the effective field dose rate from cyclotron current, spot spacing, slew time and field size were studied. Results: When scanning magnet slew time and energy switching time are not considered, single energy effective field FLASH dose rate (≥40 Gy/s) can only be achieved with less than 4 × 4 cm 2 fields when the cyclotron output current is above 500 nA. Slew time and energy switching time remain the limiting factors for achieving high effective dose rate of the field. The dose rate-time structures were obtained. The amount of the total dose delivered at the FLASH dose rate in single energy layer and volumetric field was also studied. Conclusion: It is demonstrated that while it is difficult to achieve FLASH dose rate for a large field or in a volume, local FLASH delivery to certain percentage of the total dose is possible. With further understanding of the FLASH radiobiological mechanism, this study could provide guidance to adapt current clinical multi-field proton PBS delivery practice for FLASH proton radiotherapy.